Reconfigurable FET-Based SRAM and Its Single Event Upset Performance Analysis Using TCAD Simulations. (July 2020) - Justeena, A. Nisha; Srinivasan, R.
Abstract: This work demonstrates the SRAM cell operation using planar reconfigurable devices (Reconfigurable field effect transistor - RFET). All the six devices used in the SRAM realization are identical. The N and P operations are achieved through the program gates. The cell performance is evaluated using hold, write and read static noise margins (SNM). Both the RFET and RFET-based SRAM cell are studied for their heavy ion radiation performance. The control gate of the RFET device is found to be the most sensitive region, for normal striking incidence. Single event upset (SEU) performance of the RFET based SRAM is evaluated through the critical LET (Linear Energy Threshold).